(untitled) (Mugda Medical College Journal, 2022)
Adoption of the flipped classroom approach in teaching and learning in medical education has been gaining much more popularity gradually in recent years across the globe. In Bangladesh, medical education has very little or no experience of flipped classroom teaching. Since the very beginning, most of our teaching and learning processes have been going through teacher-led didactic approach. In a traditional classroom, students often do not have the opportunity to discuss their ideas and misconceptions and there is very little interaction between students and their peers and teacher/instructor. It is assumed that this deficit is one of the main reasons for attrition in Phase-I courses (1st and 2nd Year MBBS) in anatomy, which later gives rise to failing, or dropping out exams or courses. However, in flipped classroom approach, students have opportunities to participate, selfdirect, and engage in their own learning, which supports adult learning theories, and seems beneficial to long-term learning and the development of self-directed learning skills. In this review paper, we have discussed our flipped classroom approach in anatomy teaching and learning as well as its prospects and challenges in the Phase-I of MBBS curriculum in Bangladesh. Mugda Med Coll J. 2022; 5(1): 41-45